Peran Teknologi Digital Dalam Meningkatkan Motivasi Belajar Siswa - Nurlatifah; Desma Rilla; Gusmaneli (Jurnal Pendidikan Sains dan Teknologi Terapan | E-ISSN : 3031-7983, 2025)
This study aims to analyze the role of digital technology in enhancing students’ learning motivation in the modern educational era. Technological advancements have introduced various learning innovations such as e-learning platforms, educational applications, interactive videos, and digital devices that support the learning process. Digital technology enables learning to become more engaging, flexible, and aligned with students’ individual needs and learning styles. This research employs a literature review method by examining relevant sources discussing the effectiveness of digital technology in improving learning motivation. The findings indicate that digital technology enhances both intrinsic and extrinsic motivation through diverse learning materials, appealing visual presentations, and rapid feedback. Furthermore, technology increases student engagement and enriches the learning experience. Therefore, it can be concluded that digital technology plays a significant role in creating more effective learning environments and motivating students to achieve optimal learning outcomes.